Investigation of a Prolonged and Large Outbreak of Healthcare-Associated Mucormycosis Cases in an Acute Care Hospital—Arkansas, June 2019–May 2021. (17th October 2022) - Jordan, Alexander; James, Allison E; Gold, Jeremy A W; Wu, Karen; Glowicz, Janet; Wolfe, Frankie; Vyas, Keyur; Litvintseva, Anastasia; Gade, Lalitha; Liverett, Hazel; Alverson, Mary; Burgess, Mary; et al.
Abstract: Background: Outbreaks of healthcare-associated mucormycosis (HCM), a life-threatening fungal infection, have been attributed to multiple sources, including contaminated healthcare linens. In 2020, staff at Hospital A in Arkansas alerted public health officials of a potential HCM outbreak. Methods: We collected data on patients at Hospital A who had invasive mucormycosis during January 2017–June 2021 and calculated annual incidence of HCM (defined as mucormycosis diagnosed within ≥7 days after hospital admission). We performed targeted environmental assessments, including linen sampling at the hospital, to identify potential sources of infection. Results: During the outbreak period (June 2019–June 2021), 16 patients had HCM; clinical features were similar between HCM patients and non-HCM patients. Hospital-wide HCM incidence (per 100 000 patient-days) increased from 0 in 2018 to 3 in 2019 and 6 in 2020. For the 16 HCM patients, the most common underlying medical conditions were hematologic malignancy (56%) and recent traumatic injury (38%); 38% of HCM patients died in-hospital. Healthcare-associated mucormycosis cases were not epidemiologically linked by common procedures, products, units, or rooms. At Hospital A and its contracted offsite laundry provider, suboptimal handling of laundered linens and inadequate environmental controls to prevent mucormycete contamination were observed. We detected Rhizopus on 9 (9%) of 98 linens sampled at the hospital, including on linens that had just arrived from the laundry facility. Conclusions: We describe the largest, single-center, HCM outbreak reported to date. Our findings underscore the importance of hospital-based monitoring for HCM and increased attention to the safe handling of laundered linens. Abstract : We report findings and lessons learned from an investigation of the largest, single-center, healthcare-associated outbreak of mucormycosis published to date in the United States, involving 16 patients at an Arkansas acute care hospital during June 2019–May 2021.